Development of Multilayer Microcapsules by a Phase Coacervation Method Based on Ionic Interactions for Textile Applications - Sudipta Chatterjee; Fabien Salaün; Christine Campagne (MDPI AG, 2014)
The present study describes the development of multilayer microcapsules by 11 alternate additions of chitosan (Chi) and sodium dodecyl sulfate (SDS) in a combined emulsification and phase coacervation method based on ionic interactions. After an alkali treatment, microcapsules are applied on polyester (PET) fabric by a padding process to investigate their wash-durability on fabric. Air atmospheric plasma treatment is performed on PET fabric to modify the surface properties of the textiles. Zeta potential, X-ray photoelectron spectroscopy (XPS), wetting measurements, scanning electron microscopy (SEM), and atomic force microscopy (AFM) with surface roughness measurements are realized to characterize and determine wash durability of microcapsule samples onto PET. After alkali treatment, the microcapsules are selected for textile application because they are submicron sized with the desired morphology. The results obtained from various characterization techniques indicate that microcapsules are wash-durable on PET fabric pre activated by air plasma atmospheric as Chi based microcapsules can interact directly with PET by ionic interactions.